Great white sharks [book with audioplayer] - Adamson, Thomas K., 1970- (Blastoff! readers. Shark frenzy., 2024)
"Simple text and full-color photography introduce beginning readers to great white sharks. Developed by literacy experts for students in kindergarten through third grade"-Provided by publisher"--